CLOUD-ORIENTED CAD/CAM SYSTEMS AS A MEANS OF FORMATION OF PROFESSIONAL COMPETENCES OF FUTURE MECHANICAL ENGINEERS - Rassovytska М. В. (Journal of Information Technologies in Education (ITE), 2019)
The urgency of the research is due to the contradiction between the increasing requirements for the ICT competences of mechanical engineers, in particular for the use of cloud-oriented CAD/CAM systems, on the one hand, and the insufficient use of cloud-based ICT during the training of bachelors in applied mechanics on the other hand. The purpose of the study is to distinguish cloud-oriented CAD/CAM systems, which should be used as a means of formation of the professional competencies of future mechanical engineers, and to develop methodological recommendations for their use. The importance of informational training of bachelors in applied mechanics and formation of the ability to use computer-aided design and production systems has been confirmed by an analysis of educational standards and current educational programs. Based on the analysis of various software products, AutoDesk ones were determined to be the most appropriate to use in the training of future mechanical engineers. Separate software and cloud services require the integration based on the single access that a Google Account can provide. The model of using cloud technologies as a means of formation the ICT competences of bachelors in applied mechanics was suggested. With the use of appropriate methods and forms of organizing training with the use of cloud-based ICT, as well as diagnostic tools, the expected result of the model is achieved: increasing the level of professional competence of bachelors in applied mechanics. Thus, cloud-oriented CAD/CAM systems become the leading means of building the professional competencies of future mechanical engineers, formation the ability to apply computer-aided design (CAD), that of production (CAM), and engineering research (CAE) as well as specialized application software to solve engineering problems in applied mechanics. The use of Google cloud services provides students with the opportunity to further developing of the skills of using application software to perform engineering calculations, information processing, and experimental research results treatment.